2020
DOI: 10.1186/s12943-020-01188-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of long noncoding RNAs in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most frequent subtype of primary liver cancer and one of the leading causes of cancer-related death worldwide. However, the molecular mechanisms underlying HCC pathogenesis have not been fully understood. Emerging evidences have recently suggested the crucial role of long noncoding RNAs (lncRNAs) in the tumorigenesis and progression of HCC. Various HCC-related lncRNAs have been shown to possess aberrant expression and participate in cancerous phenotypes (e.g. persistent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
308
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(338 citation statements)
references
References 178 publications
(205 reference statements)
2
308
0
Order By: Relevance
“…Many studies have shown that lots of differentially expressed lncRNAs are involved in regulation of HCC cells proliferation, migration, and invasion [2,25]. LncRNA TUG1, highly expressed in HCC cells, could promote proliferation and apoptosis of HCC cells through epigenetic silencing of KLF2 [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that lots of differentially expressed lncRNAs are involved in regulation of HCC cells proliferation, migration, and invasion [2,25]. LncRNA TUG1, highly expressed in HCC cells, could promote proliferation and apoptosis of HCC cells through epigenetic silencing of KLF2 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HIF1A-AS1 promoted starvationinduced hepatocellular carcinoma cells apoptosis by reducing HIF-1α/mTOR mediated autophagy Background Hepatocellular carcinoma (HCC) is the most common primary liver cancer in the world, and it is one of the most common causes of tumor-related deaths due to the high incidence of tumor recurrence and metastasis worldwide [1,2]. Although interventional therapy, liver transplantation, chemotherapy and surgery are available to treat HCC, the 5-year survival rate remains unsatisfactory [3,4].…”
mentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a group of RNAs that participate in the human physiological and pathological process by interacting with speci c RNAs and proteins. In recent years, lncRNAs were discovered to participate in tumor growth and progression [5]. In bladder cancer, lncRNA plays a vital role in lymphatic metastasis, epithelial-mesenchymal transformation, proliferation, migration, and apoptosis of tumor cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of most lncRNAs in liver cancer is still not understood fully, a small number of them have been extensively studied. For example, lncRNA HULC is upregulated in liver cancer and has been shown to promote liver cancer growth, metastasis, and drug resistance (Emmrich et al, 2014, Lee et al, 2015, Huang et al, 2020, Chu et al, 2011. These important roles and unique characteristics of lncRNA indicate that they have potential clinical value in the diagnosis and treatment of liver cancer.…”
Section: Introductionmentioning
confidence: 99%